The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1093/ejo/cjm130
|View full text |Cite
|
Sign up to set email alerts
|

Overjet as a predictor of sagittal skeletal relationships

Abstract: Skeletal relationships in the sagittal plane do not always correspond with dental relationships. The aim of this study was to determine in which type of malocclusion the correlation between overjet and skeletal sagittal parameters assessed by lateral cephalogram analysis is the highest. The extent to which overjet can predict skeletal relationships in the sagittal plane was also assessed. Eighty-three subjects fulfilled the inclusion criteria (40 males and 43 females, mean age 16.3 +/- 4.3 years). Overjet was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 18 publications
2
28
1
2
Order By: Relevance
“…Although in this study only dental malocclusion was evaluated, it is well documented that dental and skeletal malocclusions are interdependent [30,31] and therefore, it is valid to evaluate dental occlusal relationships to predict skeletal sagittal relationships. However, not using lateral cephalic X-ray images could be a limitation in the present study because other studies indicate that anterior vertical maxillary excess is one of the likely etiologic factors for GS [7,11,12,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in this study only dental malocclusion was evaluated, it is well documented that dental and skeletal malocclusions are interdependent [30,31] and therefore, it is valid to evaluate dental occlusal relationships to predict skeletal sagittal relationships. However, not using lateral cephalic X-ray images could be a limitation in the present study because other studies indicate that anterior vertical maxillary excess is one of the likely etiologic factors for GS [7,11,12,28].…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34] This analytical case and control study was carried out in three educational institutions in Medellin, Colombia, recruiting school children from the second to fifth grades. A population of 1,590 students was evaluated during the year September 2013 to September 2014 in order to select the case and the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Esto ocurre debido a que no existe una única prueba aceptada que determine la presencia o la severidad de la displasia esqueletal anteroposterior (32) . A pesar de ello, y de que se han reportado debilidades en relación a su desempeño en pacientes con variaciones en longitud e inclinación de la base de cráneo (19) y de los maxilares (33) , el ángulo ANB se constituye como la medida cefalométrica más comúnmente utilizada para diagnosticar las displasias sagitales esqueletales (10,19,26,(34)(35)(36) . En efecto, el uso del ángulo ANB es generalizado entre los ortodoncistas debido a que es de fácil medición, y a que sus resultados son generalmente consistentes con la presentación clínica en la mayoría de los casos.…”
Section: Discussionunclassified
“…En efecto, el uso del ángulo ANB es generalizado entre los ortodoncistas debido a que es de fácil medición, y a que sus resultados son generalmente consistentes con la presentación clínica en la mayoría de los casos. La confiabilidad de esta medida (17) se reafirma a través de su buen desempeño al evaluarse como prueba diagnóstica (10,19,26,(34)(35)(36) . Al valorar distintas medidas cefalométricas como herramienta diagnóstica, el ángulo ANB representa un test diagnóstico de alta especificidad y sensibilidad en la evaluación sagital intermaxilar.…”
Section: Discussionunclassified
“…Zupancic et al 33 reported a study to determine whether any correlation exists between overjet value, as measured on study casts, and cephalometric parameters, which evaluate the craniofacial complex in the sagittal plane. Authors concluded that for Class I and III malocclusion, overjet is not a good predictor of sagittal dysplasia; however, for Class II division 1 malocclusion, overjet is a statistically significant predictor.…”
Section: Overjet As Predictor Of Sagittal Dysplasia (2008)mentioning
confidence: 99%